The Influence of Psychological Distress on Insomnia Tendencies Among Students - A. Fatima Az-Zahra Az-Zahra; Ahmad Ridfah; Rahmat Permadi (PSPP JOURNALS, 2026)
University students often face academic, social, and personal pressures that can trigger psychological distress, such as anxiety or depression, contributing to mental health issues like insomnia. Using a quantitative approach and a correlational research design, this study aims to examine the influence of psychological distress on the tendency for insomnia among university students. A total of 574 university student respondents participated in this study, obtained through accidental sampling techniques. The average age of the respondents was 19 years. The tendency for insomnia was measured using the Insomnia Severity Index (ISI) and psychological distress was measured using the Kessler Psychological Distress Scale (K10). This study employed ordinal regression analysis. The results showed a significant effect of psychological distress (mean = 26.97, st. dev = 7.29) on the tendency for insomnia (mean = 16.84, st. dev = 4.03) among university students (pseudo-r2 = 0.184, p < 0.001). This means that the higher the level of psychological distress, the greater the tendency for insomnia among university students. This research is expected to make a significant contribution to the literature on university student insomnia by focusing on psychological distress as a potential factor.